Two-Stage Perishable Inventory Models - Goh, Chon-Huat; Greenberg, Betsy S.; Matsuo, Hirofumi (Management Science, 1993)
In this paper we consider perishable inventory systems with two types of demand. Demand may be for either fresh items or for somewhat older items. We model the system with two inventory stages. The first stage holds fresh items and the second stage holds the older items. We approximate the performance of the two-stage inventory system and compare two managerial policies.